USING ASYNCHRONOUS LEARNING IN REDESIGN: REACHING AND RETAINING THE AT-RISK STUDENT - Twigg, Carol A. (Online Learning, 2004)
Successful completion of introductory courses is critical for first-year students, but typical failure rates in these courses contribute heavily to overall institutional drop-out rates between the first and second year. Although success rates vary by institutional type and by subject matter, Research I universities commonly cite a 15 percent drop-failure-withdrawal (DFW) rate in introductory courses. Comprehensive universities’ DFW rates range from 22 percent to 45 percent in these courses. Community colleges frequently experience DFW rates of 40 percent to 50 percent or more. Most of the weaknesses attributed to large introductory courses are generic in nature and have as their source the limitations of the predominant form of instruction in U.S. colleges and universities: the didactic lecture. An overwhelming body of research shows that students do not learn effectively from lectures, and testimony from the field corroborates the literature.